PENENTUAN NILAI SPF (SUN PROTECTING FACTOR) EKSTRAK N-HEKSAN ETANOL (1:1) DARI RICE BRAN (Oryza sativa) SECARA IN VITRO DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Mulyani, Mulyani; Putri, Pramita; Wahidatullail, Nurul (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Sunlight is an energy source for the survival of living on earth, but the overexposure on the skin provides the degree of damage depends on the frequency and duration of sunlight exposure on the skin. The ability to withstand ultraviolet rays of a sunscreen is rated as Sun Protecting Factor / SPF. This study aims to determine the SPF (Sun Protection Factor) n-Hexane ethanol extract (1:1) of rice bran (Oryza sativa), using spectrophotometry UV-Vis method. Rice bran was extracted by soxhletasi using mixed solution of n-Hexane ethanol (1: 1), then prepared sample solution using absolute ethanol with the concentration series of 100 ppm, 150 ppm, 200 ppm, 250 ppm, and 300 ppm. The absorbance of solutions were then measured by UV-Vis spectrophotometer with a wavelength of 280-400 nm. Result showed that n-Heksan ethanol ekstract (1:1) of rice bran can effectively block the UV-B ray. The SPF values acquired are starting from a concentration of 200 ppm, where the SPF value is 2,355 and then at concentration of 250 ppm is 2,884 and at concentration of 300 ppm is 3.483.Keywords: Â Rice bran, Oryza sativa, sunscreen, spectrophotometry.